The palace of illusions - Divakaruni, Chitra Lekha Banerjee (Picador, 2008)
The Palace of Illusions takes us back to a time that is half-history, half-myth, and wholly magical; narrated by Panchaali, the wife of the five Pandava brothers, we are -- finally -- given a woman's take on the timeless tale that is the Mahabharata Tracing Panchaali's life -- from fiery birth and lonely childhood, where her beloved brother is her only true companion; through her complicated friendship with the enigmatic Krishna; to marriage, motherhood and Panchaali's secret attraction to the mysterious man who is her husbands' most dangerous enemy -- The Palace of Illusions is a deeply human novel about a woman born into a man's world -- a world of warriors, gods and the ever manipulating hands of fate. `A mythic tale brimming with warriors, magic and treachery' Los Angeles Times `A radiant entree into an ancient mythology . . . Charming and remarkable' Houston Chronicle `A woman's look at crime and punishment, loyalty, promises, love and vengeance . . . With The Palace of Illusions, Divakaruni has proven that her storytelling talents put her right up there with the best' Miami Herald